Montenegro, a report - José Luis Alexander Anderson Esquivel 1994- (2023)
This document contains a reflective commentary on Montenegro, a concert/ installation performed by Andervel on the 9th of May, 2023 at the Nordic house in Reykjavík. The concert marks the culmination of the studies in new media composition of the student Jose Luis Alexander Anderson Esquivel